Development of Microsoft Excel-based Interactive Media on Chemical Reaction Balancing - Ibnu Khaldun; Mustanir Mustanir; Rauzatur Rahmi (Postgraduate, University of Mataram, 2021)
All schools in general already have adequate technology and information facilities. Teachers and students can use computers as learning media usually the existing media are only in the form of powerpoints which tend to be teacher-centered, It is necessary to have interactive learning media in the learning process, one of which is Microsoft excel-based interactive media on chemical reaction equalization material, especially metathesis reactions. The name of the developed media is Chem React, which is a chemical reaction. This study aimed to determine the feasibility of Chem React media as a chemistry learning medium and to determine the responses of teachers and students to the development of Chem React media. This study uses the ADDIE research and development model. The sampling technique was carried out by purposive sampling, namely 15 students who were able to use computers and ten chemistry teachers. The procedure for collecting data was needs analysis, design, development, validation, media revision, small-scale testing, and evaluation. Data analysis techniques calculated the feasibility of the media, student, and teacher responses. The results of the feasibility assessment by media and material experts obtained an average rating of 92.97%, in the very good category. The results of teacher responses of 91.50% and student responses of 90.33% fall into the very good category. So the Chem React media is very suitable to be used as a learning medium on chemical reaction balancing material